2015
DOI: 10.1016/j.jacc.2014.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Interactome of Serine/Threonine Protein Phosphatase Type-1 in Atrial Fibrillation Patients

Abstract: BACKGROUND Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, yet current pharmacological treatments are limited. Serine/threonine protein phosphatase type-1 (PP1), a major phosphatase in the heart, consists of a catalytic subunit (PP1c) and a large set of regulatory (R)-subunits that confer localization and substrate specificity to the holoenzyme. Previous studies suggest that PP1 is dysregulated in AF, but the mechanisms are unknown. OBJECTIVES The purpose of this study was to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…[5] For example, the phosphorylation levels of myosin binding protein-C and of the L-type Ca 2+ channel were decreased whereas the phosphorylation levels of phospholamban (PLN) and ryanodine receptor 2 (RyR2) were increased. [4, 5, 8] On the other hand, in patients with paroxysmal AF, there is no significant change in the expression levels of PP1c,[9] yet the phosphorylation of at least one target protein, PLN, is increased. [9, 10] Finally, in experimental AF models, both unchanged PP1c levels with or without increased PP1c activity have been reported, and again with inconsistent changes in the phosphorylation of its known targets.…”
Section: Fundamental Challenge In Studying Pp1mentioning
confidence: 99%
See 3 more Smart Citations
“…[5] For example, the phosphorylation levels of myosin binding protein-C and of the L-type Ca 2+ channel were decreased whereas the phosphorylation levels of phospholamban (PLN) and ryanodine receptor 2 (RyR2) were increased. [4, 5, 8] On the other hand, in patients with paroxysmal AF, there is no significant change in the expression levels of PP1c,[9] yet the phosphorylation of at least one target protein, PLN, is increased. [9, 10] Finally, in experimental AF models, both unchanged PP1c levels with or without increased PP1c activity have been reported, and again with inconsistent changes in the phosphorylation of its known targets.…”
Section: Fundamental Challenge In Studying Pp1mentioning
confidence: 99%
“…[4, 5, 8] On the other hand, in patients with paroxysmal AF, there is no significant change in the expression levels of PP1c,[9] yet the phosphorylation of at least one target protein, PLN, is increased. [9, 10] Finally, in experimental AF models, both unchanged PP1c levels with or without increased PP1c activity have been reported, and again with inconsistent changes in the phosphorylation of its known targets. [6, 8, 1114]…”
Section: Fundamental Challenge In Studying Pp1mentioning
confidence: 99%
See 2 more Smart Citations
“…Chiang et al recently elucidated the interactome of the protein phosphtase 1 catalytic subunit (PP1c), identifying 78 interacting partners in human heart. The proteomics results found increased binding to PDE5A in paroxysmal atrial fibrillation patients to impair proteins involved in electrical and calcium remodeling, a result that has implications in the understanding and treatment of atrial fibrillation [80]. Waldron et al identified the TBX5 interactome in the developing heart to discover its interactions with the repressor complex NuRD, elucidating the mechanisms by which TBX5 mutations can influence cardiac development and confer congenital heart diseases.…”
Section: Examples and Frontiers In Cardiovascular Applicationsmentioning
confidence: 99%